Study of Negative Elements for Discrete Mechatronic Systems - Buchacz, Andrzej; Ga, Damian (Discontinuity, Nonlinearity, and Complexity, 2026)
In the paper, the known problem of vibration control have been studied for elements which have defined configurations and connections of piezostack actuator with external electric network and can exhibits negative values. Depending on the phase of the synthesis process, used for the design of the mechatronic systems that have to comply with some given requirements, negative elements have been identified and described. Subsequently with the study on selection of corresponding negative stiffness and damping, presented in the graph form, optimal values for the systems can be compared. Following examples with selected calculations, the goal of this paper is to present limits and constrains that may support the physical realization, as well as applications of the considered systems.